Uji Aktivitas Antiseptik Ekstrak Etanol Daun Sirih (Piper betle Linn.) dalam Obat Kumur terhadap Staphylococcus aureus secara in Vitro - Sundari, Dian; Almasyhuri, Almasyhuri (Jurnal Kefarmasian Indonesia, 2019)
Betle leaf (Piper betle Linn.) is very popular in Indonesia. Betle leaf is useful for dental health and frequently used as mouthwash; to eliminate body and mouth odor; treats mouth ulcer, nosebleed, itching, ulceration and vaginal discharge in women. An oral cavity is a place for bacteria. If there is a bacterial immunity reduction, that was originally commensal bacteria can turn into a pathogen that cause infection. One of bacteria that commonly found in the oral cavity is Staphylococcus aureus. The bacteria have the ability to occupy and form biofilm on biomaterials that cause resistant to antimicrobials, thus making it difficult to eradicate host that is infected by S. aureus. Previous study reported a multidrug resistant of S. aureus that could cause death, that to overcome it, betle leaves extract ethanol in vitro antiseptic test to S.aureus was conducted. The test was conducted by the phenol coefficient method using S. auereus ATCC 25923 bacteria. Povidone iodine mouthwash that is circulated in the market is used as a comparison. The results showed that mouthwash containing ethanol extract of betle leaf had a phenol coefficient value of 1.87 while povidone iodine mouthwash as a comparison, had a phenol coefficient of 1.0. Mouthwash containing ethanol extract of betle leaf had higher antiseptic effectiveness than the comparative mouthwash.